Learning Guidance and Counseling Services to Support Student Learning in Junior High Schools - Moch. Arifudin; Firda Af’idatun Nisa’; Mariana Rahmawati Erna Ningrum; Lukmanah Nabilah; Annisa Dwi Fariha Bin Yasak (Universitas Al-Falah As-Sunniyah Kencong Jember, 2026)
Guidance and counseling (BK) services play an important role in supporting student learning in junior high schools, but their implementation still faces various challenges influenced by student characteristics, family environment, and the development of digital technology. This study aims to explore the implementation of learning guidance and counseling services in supporting student learning in junior high schools. The study used a qualitative approach with a multiple case study design. The research participants consisted of four BK teachers from four junior high schools in the South Jember region who were selected using purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis, while data validity was maintained through source triangulation and member checking. The results of the study identified six main themes, namely (1) needs assessment as the basis for services, (2) academic and psychosocial assistance, (3) collaboration between BK teachers, subject teachers, homeroom teachers, and parents, (4) factors causing learning difficulties including personal, family, and digital technology aspects, (5) intervention strategies based on student needs, and (6) indicators of success characterized by increased motivation, learning independence, emotional regulation, and self-confidence. The findings indicate that learning guidance and counseling services have shifted from a curative approach to a preventive and developmental approach focused on developing students' potential. This study confirms that assessment-based, collaborative, and responsive guidance and counseling services are essential components in creating effective, inclusive, and sustainable learning in junior high schools.